Analysis of Thermal Performance Improvement of Engine Fins by Varying the Materials and Profiles Used at High Temperatures - Pallepogu Naveen; Sri. M. Kumara Swamy (International Journal of Energy and Thermal Applications, 2024)
In this thesis, we will design fins using various profiles and materials to identify the optimal combination for a 100cc engine. We will also test different materials for fins to evaluate the engine's heat efficiency. Our study will involve a comparison between the optimized fins and the original aluminum fins currently used. To ensure the optimal performance of the 100cc engine, we will utilize advanced analytical software to thoroughly analyze the results from our simulations. This analysis will help us identify the most efficient fin design for engine cooling, which will then be further optimized using ANSYS. A key focus of the study will be testing and evaluating the performance of four different materials—Al 6082, Magnesium alloy, Al + SiC-12, and Al 8011A. These materials will be analyzed in combination with varying fin profiles, adjusting their shapes to enhance heat dissipation. The design phase of the single-cylinder block will be conducted using CATIA, where different fin arrangements will be created. Subsequently, ANSYS will be employed to carry out the detailed analytical analysis, allowing us to assess the thermal performance of each design and material combination. This iterative process will ensure that the most efficient configuration of materials and fin profiles is achieved, leading to improved engine cooling efficiency.
Keywords: Material comparison; engine cooling; materials testing; single-cylinder block; thermal analysis